2009
DOI: 10.1073/pnas.0907631106
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin is a multifunctional factor in spermatogenesis

Abstract: Trypsin is well known as a pancreatic enzyme that is typically secreted into the intestine to digest proteins. We show in our current study, however, that trypsin is also a key factor in the control of spermatogenesis. A progestin in teleost fish, 17␣, 20␤-dihydroxy-4-pregnen-3-one (DHP), is an essential component of the spermatogenesis pathway, particularly during the initiation of the first meiotic division. In the course of our investigations into the mechanisms underlying progestin-stimulated spermatogenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…However, the results of long-term (15 days) organ culture showed that taurine cannot induce complete spermatogenesis. Consistent with this finding, we reported previously that trypsin is also up-regulated in eel testis by DHP and that it induces the expression of Spo11 in germ cells, but not all aspects of spermatogenesis (Miura et al 2009). These results collectively suggest that meiosis is controlled by the conglomeration of various factors including taurine and trypsin.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…However, the results of long-term (15 days) organ culture showed that taurine cannot induce complete spermatogenesis. Consistent with this finding, we reported previously that trypsin is also up-regulated in eel testis by DHP and that it induces the expression of Spo11 in germ cells, but not all aspects of spermatogenesis (Miura et al 2009). These results collectively suggest that meiosis is controlled by the conglomeration of various factors including taurine and trypsin.…”
Section: Discussionsupporting
confidence: 86%
“…Several cDNA clones that are regulated by DHP were thereby identified (Ozaki et al 2006a, b;Miura et al 2009), one of which showed a high homology to cysteine dioxygenase 1 (CDO1) in other animals. CDO is one of the enzymes that catalyze the conversion of L-cysteine to cysteine sulfinate (cysteine sulfinic acid).…”
Section: Introductionmentioning
confidence: 99%
“…late type B spermatogonia) were less intensely/not stained. In Japanese eel, the molecular mechanism underlying DHPmediated stimulation of spermatogenesis involved elevated expression of 11b-hydroxysteroid dehydrogenase and trypsinogen in Leydig and Sertoli cells respectively , Miura et al 2009). The Sertoli cell expression that we report is consistent with the presence of Pgr in testicular somatic cells in vertebrates, but we could not detect pgr mRNA in Leydig cells.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence indicates that progestins exert regulatory functions at early stages of fish spermatogenesis. For example, in Japanese eel (Anguilla japonica) DHP stimulated spermatogonial DNA synthesis and the initiation of meiosis, by inducing expression of the short form of 11b-hydroxysteroid dehydrogenase (Hsd11b) in Leydig cells and of trypsinogen in Sertoli cells [18,19].…”
Section: Introductionmentioning
confidence: 99%